(untitled) (Jurnal Riset Manajemen Akuntansi Indonesia, 2025)
This study aims to improve the performance of the employees of the Regional Technical Implementation Unit for Road Maintenance and Irrigation of the Public Works and Spatial Planning of Temanggung Regency in irrigation maintenance operational activities. One of the efforts in employee development is to provide human resource training, especially during a pandemic like this, employees are expected to continue to develop or improve skills and be able to compete in the era of digitalization which is growing rapidly. Performance is a result achieved by employees in their work according to certain criteria that apply to a job. Performance measurement can use aspects: quality of work, quantity of work, implementation of duties and responsibilities. The research was carried out from February to March 2022. This type of research was descriptive qualitative. Interview data collection. Data analysis interactive model of analysis. The results showed that: 1) The performance of UPTD PJP DPUPR employees in Temanggung Regency was not on target due to: supervisory staff (irrigation minister) for supervising the implementation of Irrigation OP staff not yet understanding the main tasks and functions, there was no daily/weekly/monthly work plan (implementation of work). not planned and systematic) to facilitate the division of tasks to Irrigation OP officers, human resources (irrigation OP workers) who are not yet competent in the irrigation sector are still not compact in group work, a lot of time is wasted (long breaks, late arrival and early return), some farmers are still not doing well. 2) Efforts that can be made to improve the performance of employees at UPTD PJP DPUPR Temanggung Regency, namely: need to understand the duties and functions and add supervisors/manteries, need debriefing and direction as well as weekly/monthly monitoring and evaluation, determine work plans before carrying out workers/ the task of making irrigation OP staff comfortable and compact, increasing public awareness, especially farmers/water user communities (P3A) in maintaining irrigation networks for the common good and increasing the competence of human resources (irrigation OP workers) through training according to their respective fields.